Designing photolabile ruthenium polypyridyl crosslinkers for hydrogel formation and multiplexed, visible-light degradation - Rapp, Teresa L. (RSC Adv, 2019)
Photoresponsive materials afford spatiotemporal control over desirable physical, chemical and biological properties. For advanced applications, there is need for molecular phototriggers that are readily incorporated within larger structures, and spatially-sequentially addressable with different wavelengths of visible light, enabling multiplexing. Here we describe spectrally tunable (λ(max) = 420–530 nm) ruthenium polypyridyl complexes functionalized with two photolabile nitrile ligands that present terminal alkynes for subsequent crosslinking reactions, including hydrogel formation. Two Ru crosslinkers were incorporated within a PEG–hydrogel matrix, and sequentially degraded by irradiation with 592 nm and 410 nm light.